From data to evidence in English language research - Suhr, Carla; Taavitsainen, Irma; Nevalainen, Terttu (Language and computers, 2019)
1. Corpus linguistics as digital scholarship big data, rich data and uncharted data / Terttu Nevalainen, Carla Suhr and Irma Taavitsainen -- 2. Big Data Opportunities and Challenges for English Corpus Linguistics / Antoinette Renouf -- 3. Corpus-based Studies of Lexical and Semantic Variation: The Importance of Both Corpus Size and Corpus Design / Mark Davies -- 4. Empirically Charting the Success of Prescriptivism: Some Case Studies of Nineteenth-century English / Lieselotte Anderwald -- 5. Warn Against -ing Exceptions to Bach's Generalization in Four Varieties of English / Mark Kaunisto and Juhani Rudanko -- 6. Commonplace Books Charting and Enriching Complex Data / Thomas Kohnen -- 7. Mining Big Data -- a Philologist's Perspective / Tanja Rutten -- 8. Function-to-form Mapping in Corpora Historical Corpus Pragmatics and the Study of Stance Expressions / Daniela Landert -- 9. Scholastic Argumentation in Early English Medical Writing and its Afterlife: New Corpus Evidence / Irma Taavitsainen and Gerold Schneider -- 10. Language Surrounding Poverty in Early Modern England: A Corpus-based Investigation of How People Living in the Seventeenth-century Perceived the Criminalised Poor / Tony McEnery and Helen Baker -- 11. An Information-Theoretic Approach to Modeling Diachronic Change in Scientific English/ Stefania Degaetano-Ortlieb, Hannah Kermes, Ashraf Khamis and Elke Teich -- 12. Academic Vocabulary in Wikipedia Articles Frequency and Dispersion in Uneven Datasets / Turo Hiltunen and Jukka Tyrkko -- 13. Words (don't come easy): The Automatic Retrieval and Analysis of Popular Song Lyrics / David Brett and Antonio Pinna -- 14. Charting New Sources of elf Data: A Multi-genre Corpus Approach / Mikko Laitinen, Magnus Levin and Alexander Lakaw